Krisis Ekosistem Perairan di Merauke: Strategi Pengelolaan Berbasis Kearifan Lokal dan Data Spasial: Studi Kasus di Kampung Yanggandur, Distrik Sota - Chalvyn Silasa Pakidi (Jurnal Pustaka Cendekia Pendidikan, 2024)
This study aims to analyze the damage to the aquatic ecosystem in Yanggandur Village, Sota District, Merauke, and to identify the values ​​of local wisdom of the Marind indigenous community in managing aquatic resources. In addition, this study formulates a sustainable management strategy that integrates spatial technology and local wisdom in a participatory manner. The method used is a qualitative-descriptive approach with a case study design. Data were obtained through in-depth interviews, participatory observation, satellite imagery analysis (Landsat and Sentinel), and review of related documents. Qualitative data analysis used thematic techniques with the help of NVivo, while spatial data was processed with GIS software (QGIS and ArcGIS). Triangulation of sources and methods was applied to ensure the validity of the findings. The results of the study showed a significant decrease in the area of ​​water bodies and the quality of aquatic ecosystems due to anthropogenic pressures and changes in land use. The local wisdom of the Marind indigenous community has proven effective in maintaining the sustainability of resources, despite the challenges of modernization. Spatial mapping provides a picture of critical zoning that supports more appropriate and participatory management decision-making. This study recommends synergy between local wisdom and spatial technology as the main strategy for sustainable management of aquatic ecosystems in Merauke. Community empowerment and increasing technological capacity are key factors in realizing inclusive, adaptive, and sustainable management of aquatic resources. This study provides an important contribution to natural resource management policies in customary areas that have high ecological and cultural values.